Impact of ultrasound processing on some milk-borne microorganisms and the components of camel milk - Dhahir, Namariq; Feugang, Jean; Witrick, Katherine; Park, Seongbin; AbuGhazaleh, Amer (Emirates Journal of Food and Agriculture, 2020)
Inactivation of pathogenic bacteria Escherichia coli O157: H7 and Salmonella Typhimurium in camel milk was investigated using ultrasound processing (900 W, 20 kHz, 100% power level). In addition, the effect of ultrasound treatment on raw camel milk components was studied to detect changes in fatty acid profile, lipid peroxides, protein fractions, and volatile compounds. Bacterial strains (106 CFU/ml) were added to pasteurized camel milk samples (70 ml) and transferred into a sterile aluminum container (30 mm x 120 mm, 100-ml total capacity) and then subjected to continuous ultrasound processing for 15 min in an ice water bath using a 13-mm diameter probe. The standard plate count (SPC) agar method and the in vivo imaging system (IVIS) were used to evaluate the viability of bioluminescence-transformed bacteria (E. coli O157: H7 and S. Typhimurium). The continuous ultrasound processing of camel milk resulted in significant (P<0.05) reductions in S. Typhimurium and E. coli O157: H7. Relative to unsonicated raw camel milk, the cis-9, trans-11 conjugated linoleic acid (CLA) and trans-10, cis-12 CLA contents were not affected (P>0.05) by the ultrasound processing. The TBAR values, a marker of lipid peroxidation, and milk protein fractions were also similar (P>0.05) between the sonicated and unsonicated raw camel milk. A total of 24 volatile compounds (VC) were identified including 8 aldehydes, 3 ketones, 5 acids, 5 esters, 2 aromatic hydrocarbonate, and 1 sulfo compound. Of these 24 VC, eleven VC increased (P<0.05) and seven decreased (P<0.05) after sonication. In conclusion, the results of this study showed that ultrasound processing of camel milk was efficient in inactivating subsets of milk-borne pathogens without detrimental effects on camel milk fatty acids, lipid peroxides, and protein fractions. However, there were some changes in milk VC which may affect the sensory quality of milk.